Towards intelligent manufacturing - Lemos, Marilza A. [UNESP]; Liberado, Eduardo V. [UNESP]; Marques, Marcio A. [UNESP]; Botura Jr., Galdenoro [UNESP] (Elsevier, 2007)
This article describes the application of an Artificial Intelligence Planner in a robotized assembly cell that can be integrated to a Flexible Manufacturing System. The objective is to allow different products to be automatically assembled in a single production line with no pre-established assembly plans. The planner function is to generate action plans to the robot, in real time, from two input information: the initial state (disposition of parts of the product in line) and the final state (configuration of the assembled product). Copyright © 2007 IFAC.
Keywords: Artificial intelligence; Assembly robot; Intelligent manufacturing systems; Manufacturing processes; Planning; Action plan; Assembly cells; Final state; In-line; Initial state; Intelligent Manufacturing; Intelligent manufacturing system; Production line; Real time; Assembly; Cost effectiveness; Intelligent robots; Product development; Real time systems; Flexible manufacturing systems